High peak and high average radiofrequency power transmit/receive switch for thermal magnetic resonance. Issue 5 (1st April 2018) - Ji, Yiyi; Hoffmann, Werner; Pham, Michal; Dunn, Alexander E.; Han, Haopeng; Özerdem, Celal; Waiczies, Helmar; Rohloff, Michael; Endemann, Beate; Boyer, Cyrille; Lim, May; Niendorf, Thoralf; et al.
Abstract : Purpose: To study the role of temperature in biological systems, diagnostic contrasts and thermal therapies, RF pulses for MR spin excitation can be deliberately used to apply a thermal stimulus. This application requires dedicated transmit/receive (Tx/Rx) switches that support high peak powers for MRI and high average powers for RF heating. To meet this goal, we propose a high‐performance Tx/Rx switch based on positive‐intrinsic‐negative diodes and quarter‐wavelength (λ/4) stubs. Methods: The λ/4 stubs in the proposed Tx/Rx switch design route the transmitted RF signal directly to the RF coil/antenna without passing through any electronic components (e.g., positive‐intrinsic‐negative diodes). Bench measurements, MRI, MR thermometry, and RF heating experiments were performed at f  = 297 MHz (B0  = 7 T) to examine the characteristics and applicability of the switch. Results: The proposed design provided an isolation of −35.7dB/−41.5dB during transmission/reception. The insertion loss was −0.41dB/−0.27dB during transmission/reception. The switch supports high peak (3.9 kW) and high average (120 W) RF powers for MRI and RF heating at f  = 297 MHz. High‐resolution MRI of the wrist yielded image quality competitive with that obtained with a conventional Tx/Rx switch. Radiofrequency heating in phantom monitored by MR thermometry demonstrated the switch applicability for thermal modulation. Upon these findings, thermally activated release of a model drug attached to thermoresponsive polymers was demonstrated. Conclusion: The high‐power Tx/Rx switch enables thermal MR applications at 7 T, contributing to the study of the role of temperature in biological systems and diseases. All design files of the switch will be made available open source at www.opensourceimaging.org .